Pengembangan Materi Pembelajaran Digital untuk Teknik Passing Bawah Tangan Dasar Bola Voli di Sekolah Dasar Negeri Sigong - Ade Setia Maulana; Dewi Wahyuni; Adiman Adiman (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. The purpose of this study is to implement the development of digital teaching materials on basic volleyball techniques at SDN 4 Sigong. The teaching materials resulting from the development research were tested for validity and usability. Materials and methods. This research was conducted from April to September 2024 at SDN 4 Sigong. The subjects of this research were expert lecturers and teachers of physical education and health. The instrument used for this research was a questionnaire. Data analysis techniques used percentage formulas. Results. The results of the study, as seen from the validation results, were 91.1% for physical education teachers, 95.5% for expert lecturers in physical education 1, 89.7% for expert lecturers in physical education 2, and 88.2% for physical education teachers. These percentages resulted in a final score of 91.1%. These percentages meet the criteria for high validity. These percentages meet the criteria for high validity. Conclusion. Thus, the teaching material on the basic technique of underhand volleyball passing can be used as alternative or supporting teaching material in teaching the basic techniques of volleyball to sixth-grade primary school students.